Towards Sustainable Lactic Acid Production: Avoiding Gypsum as a Byproduct by using Selective Liquid‐Phase Adsorption. Issue 15 (24th June 2019) - Rübenach, Lukas; Lins, Jonas; Koh, Ezra; Rose, Marcus
Abstract: The utilization of biomass is one of the major challenges for the transition from fossil to renewable resources. Often, the separation of the desired product from the reaction mixture is the most energy‐intensive step. Liquid‐phase adsorption is a promising separation technology that could significantly improve downstream processing in biorefineries. Highly hydrophobic adsorbents were applied for the separation of lactic acid (LA) from aqueous solutions and to avoid the formation of gypsum as a byproduct. High uptakes and selectivity were obtained in single‐solute and co‐adsorption experiments. Porous hyper‐crosslinked polymers (HCP) and polymer‐based spherical activated carbon performed best and showed excellent selectivity for the selective removal of LA. Desorption experiments revealed that HCP was the ideal adsorbent for the separation of LA from aqueous solution and enabled the production of gypsum‐free LA. Abstract : Bye bye byproduct ! Lactic acid can be selectively removed from fermentation mixtures by adsorption on highly hydrophobic adsorbents. The formation of gypsum as a byproduct is avoided, and a much more sustainable production process is enabled. The best results are obtained with porous hyper‐crosslinked polymers and polymer‐based spherical activated carbon.